'Birthplace unknown': on the symbolic value of the passport for identity-construction among naturalised citizens. Issue 1 (2nd January 2023) - Bivand Erdal, Marta; Midtbøen, Arnfinn H
ABSTRACT: When naturalised citizens receive their passport, it is material and symbolic proof of membership in the nation-state, tying the individual to the nation and providing mobility resources. For naturalised Norwegian citizens, their birthplace appears in the passport. What might be the implications of removing this information? In 2016, the Norwegian government replaced birthplace details with 'birthplace unknown' in the passports of naturalised citizens from 31 Asian and African countries. Drawing on this case and 41 in-depth interviews with people of different citizenship-statuses, we analyse the role of the passport and birthplace information in it for naturalised citizens' identity-construction. The procedural change led to an experience of devalued citizenship in practical, emotional, and symbolic ways, by those directly affected and others, showing the precariousness of identity for naturalised citizens. We find that the passport matters for identity-construction, as a symbol of national belonging, and suggests more-than-instrumental approaches to citizenship among immigrant populations.